Indian LIS Job Market and its Visibility through Portals and Mailing Lists/Forums - Sawant, Sarika; Sawant, Prachi (Journal of Information and Knowledge, 2017)
The main aim of the study was to explore how marketing of LIS jobs is done through Mailing list/Portal. Content analysis method was applied considering job advertisements for Library and Information professionals that appeared from January 2014 to December 2014 in mailing lists & Portal. The analysis of jobs were done by considering pointers such as number, month-wise, state-wise, nature of appointment, job description etc. It was observed that maximum number of job ads were posted during first half of the year, January receiving high number of job ads. The maximum number of ads posted was of General category. It was observed that more than half of job ads posted were of temporary/contractual nature. It was noted that almost 3/4 job ads were posted for Academic Libraries. It was found that half of the job ads came with full job description whereas half mentioned a link to the original ad appearing in respective universities website/newspaper.